2013
DOI: 10.1155/2013/596496
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Induces Mitochondrial Mediated Apoptosis and Protective Autophagy in Human Glioblastoma U373MG Cells

Abstract: Quercetin is a dietary flavonoid with known antitumor effects against several types of cancers by promoting apoptotic cell death and inducing cell cycle arrest. However, U373MG malignant glioma cells expressing mutant p53 are resistant to a 24 h quercetin treatment. In this study, the anticancer effect of quercetin was reevaluated in U373MG cells, and quercetin was found to be significantly effective in inhibiting proliferation of U373MG cells in a concentration-dependent manner after 48 and 72 h of incubation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 47 publications
(41 reference statements)
6
96
1
2
Order By: Relevance
“…In addition, treatment with melatonin also reduces autophagy in the liver of ob/ob mice, or in morphine‐treated rat neurons , and in both cases, autophagy reduction is beneficial. Therefore, melatonin modulation of autophagy seems to be cell‐type‐ and context‐dependent, similar to other antioxidant molecules with analog properties .…”
Section: Discussionmentioning
confidence: 89%
“…In addition, treatment with melatonin also reduces autophagy in the liver of ob/ob mice, or in morphine‐treated rat neurons , and in both cases, autophagy reduction is beneficial. Therefore, melatonin modulation of autophagy seems to be cell‐type‐ and context‐dependent, similar to other antioxidant molecules with analog properties .…”
Section: Discussionmentioning
confidence: 89%
“…Death signals have been reported to be able to induce p53 translocation to the mitochondria via the transcription-independent apoptotic signal (3538). p53 participates directly in the intrinsic apoptosis pathway by interacting with the multidomain members of the Bcl-2 family to induce mitochondrial outer membrane permeabilization, regardless of several common mutations (3941). In the present studies, we observed that for mitomycin C, the combinatorial treatment, as well as hypoxic conditions, induced translocation of p53 protein to the mitochondria, while the application of bortezomib had a limited effect on p53 elevation and mitochondrial translocation.…”
Section: Discussionmentioning
confidence: 99%
“…In U373MG malignant glioma cells quercetin induced mitochondrial apoptosis via cytochrome-c release and accumulation of reactive oxygen species as evidenced by more cells in the sub-G1 phase, the appearance of fragmented nuclei, decreased mitochondrial membrane potential, activation of caspase-3 and caspase-7, and degradation of the poly(adenosine di-phosphate-ribose) polymerase protein. 67 In these cell cultures, quercetin also induced protective autophagy.…”
Section: Succinatementioning
confidence: 85%